Um estudo de concepções e experiências de escolas de tempo integral nos municípios de Campinas e Jundiaí - Cheroti, Aparecida do Carmo Fernandes (2019)
The present study aims to analyze the concept of integral education in different historical contexts and the unfolding of the concept as public educational policy. Taking this reference, the insertion of the concept into the official Brazilian documents guiding integral education was analyzed, and finally, its formulation and effectiveness as public educational policy, focusing on two municipal experiences developed in the State of São Paulo. The concept of integral education was present in historical pedagogical conceptions, such as the Paideia, originated in Ancient Greece, passing through the French Revolution, reappearing at the International Congress of Workers in 1868, in the omnilateral formation of Marx and Engels and in the Unitarian School of Gramsci. It was also explored the concept of integral formation of the individual through the perspective of social law provided for in the Constitution of 1988 and in the Law of Guidelines and Bases of Education (9394/1996), as well as analyzing how the full- of educational public policies based and formulated in integral education, is linked or not to the first concepts of this educational model. Based on these assumptions, the analysis of two public educational policies related to integral education in the State of São Paulo was analyzed, with the central question: Education policy formulated in some municipalities of São Paulo.The research was carried out in the steps of bibliographical survey and documentary analysis. The final analysis of the experiments illustrates that there is still a gap between the design of a project and its implementation, and that the fragmentation of content as well as teaching dissociated from social action and educational work hinders the municipal experiences of fulltime municipalities of Jundiaí and Campinas can be considered a integral education according to the formulations and concepts covered in the dissertation. This paper intends to contribute to the discussion about the formulation and execution of municipal public policies by analyzing the guidelines contained in the official documents and the effective practice related to integral education.